Abuso de cocaína no parenteral en pacientes infectados con el Virus de la Inmunodeficiencia Humana - Jerí, F.R.; Ramírez, J.; Castañeda, M.A.; Pérez, J.C.; Lucho, M.L.; Terán, A.; Wong, J.A.; Villa, R.; Durán, L. (Revista de Neuro-Psiquiatría, 2013)
.